Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijerph18126190
|View full text |Cite
|
Sign up to set email alerts
|

Confinement Situation of the Spanish Population during the Health Crisis of COVID-19: Resilience Mediation Process in the Relationship of Dispositional Optimism and Psychological Well-Being

Abstract: The pandemic generated by COVID-19 is one of the most complex challenges humanity has faced in recent years. This study aims to explore the levels of dispositional optimism, resilience and psychological well-being in the sociodemographic and economic situation produced during the state of alarm and to investigate the resilience mediation between optimism and psychological well-being. The sample included 566 volunteers from Spain (73.5% women; M = 40.2 years, SD = 12.8). An ad hoc questionnaire was applied to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…38 When it comes to the relationship between demographic characteristics and the variables studied, analyses showed that older people scored higher, while adolescents and students showed lower levels of optimism and life satisfaction, confirming previous research. 39 Bozkurt and Aytaç 40 argue that the relationship between age and life satisfaction, which was U-shaped before the pandemic, changed after the epidemic, with the group most affected by the reduction in life satisfaction being those under 25 years of age. Gender is also an important variable that differentiates the experience of optimism and life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…38 When it comes to the relationship between demographic characteristics and the variables studied, analyses showed that older people scored higher, while adolescents and students showed lower levels of optimism and life satisfaction, confirming previous research. 39 Bozkurt and Aytaç 40 argue that the relationship between age and life satisfaction, which was U-shaped before the pandemic, changed after the epidemic, with the group most affected by the reduction in life satisfaction being those under 25 years of age. Gender is also an important variable that differentiates the experience of optimism and life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“… Demetriou et al (2021) found that hopefulness, together with age and educational attainment, significantly predicted psychological resilience and willingness and capacity to adapt to COVID-19 measures during the early stages of the pandemic in a sample of Greek and Cypriot adults. Zayas et al (2021) found that dispositional optimism was significantly associated with the psychological well-being of Spanish adults, and this association was mediated by resilience. This might suggest that optimism is an antecedent of resilience.…”
Section: Introductionmentioning
confidence: 90%
“…A study by Zayas et al ( 2021 ) points to the need for interventions to promote resilience for the general population in times of pandemic, alluding to the study on the preliminary analyzes of the “Resilience and Well-being Programme: Stay at Home” (Sánchez-Hernández and Canales, 2020a , b ), which is a psycho-educational intervention applied in confinement and de-escalation of the first wave of the pandemic in Spain, to promote well-being and prevent emotional problems (see Table 1 ). The sample consisted of 259 participants, 68.3% women and 31.7% men, with a mean age of 39.33 years (SD = 14.3).…”
Section: Promotion Of Resilience In Families In the Face Of Confineme...mentioning
confidence: 99%